Comparative efficacy of 0.1% and 0.15% Sodium Hyaluronate on lipid layer and meibomian glands following cataract surgery: A randomized prospective study. - Seung Ahn Yang; Mu Ryang Jeong; Cheon Ho Park; Ki Bum Cheon; Jun Ho Chang; Ji Eun Lee (PLoS ONE)
Purpose To compare the efficacy of a 0.15% HA with that of 0.1% HA eye drops for DES after cataract surgery. Methods This study was double blinded, randomized and prospective study, and conducted in 69 participants (70 eyes) from Pusan National University Yangsan Hospital and executed from February 1, 2022 to November 30, 2022. Participants were adult cataract patients with normal lid position, not suffering from any other ocular disease and not meet the exclusion cirteria of clinical trial. Participants were randomly divided into two groups: 35 participants (17 males and 18 females) in the 0.1% HA group and 34 participants (19 males and 15 females) in the 0.15% HA group, receiving treatment six times daily for 6 weeks following cataract surgery. Subjective and objective assessments were performed at preoperative and postoperative visits, including ocular surface disease index score, tear break up time, corneal staining score, Schirmer's I test score, lipid layer thickness), meiboscore, and biochemical analysis of the eye drops. Results Throughout the study, the postoperative ocular surface disease index score was significantly lower in the group receiving 0.15% hyaluronic acid than in the group receiving 0.1% hyaluronic acid. Additionally, the postoperative ocular surface disease index score showed a significant positive correlation with the postoperative use of 0.15% hyaluronic acid and the preoperative Schirmer's I test score. In multivariate analysis, treatment with 0.15% hyaluronic acid and the preoperative ocular surface disease index score were significant independent parameters affecting the postoperative ocular surface disease index score. Conclusion The use of 0.15% hyaluronic acid is recommended for its potential advantages in alleviating symptoms following cataract surgery, making it a viable alternative to traditional 0.1% hyaluronic acid treatment. Trial registration ISRCTN95830348.